Characterizing Hematological Changes Following Repeated Exposure to Non-Targeted Low-Dose Ionizing Radiation in Prostate Cancer Patients - Allison E. Kennedy; Ian S. Dayes; Sameer Parpia; Douglas R. Boreham; Dawn M. E. Bowdish (SAGE Publishing, 2024)
The duration and magnitude of haematological changes following non-targeted low-dose radiation have not been well explored. We previously reported that low-dose radiation (150 mGy 2x/week for 5 consecutive weeks) was well tolerated by participants (n = 15) with minimal toxicities and no changes in quality of life. Leukocytes, platelets and erythrocytes decreased from baseline measurement 12 months following treatment, however changes were not clinically significant. T-cells, NK-cells, B-cells and neutrophils were found to decrease during treatment and return to baseline levels by 3 months. The monocyte activation marker CD64 (FcγRI) was lower in participants whose cancer did not progress during the 12 month study follow up period, potentially giving insights into a biomarker of treatment success. Herein, we provide one of the most detailed descriptions of hematologic changes during low dose radiation treatment and during one year follow up. Low-dose radiation was associated with minor hematologic changes that mostly resolved by 3 months. (Clinical Trial Registered with the United States National Library of Medicine and National Institutes of Health under the title 'Low Dose Hemi-Body Radiation for Recurrent Prostate Cancer'; ID: NCT03196778).